Pemberdayaan Ekonomi Masyarakat Melalui Home Industry - Yuyun Yuniarsih; Enok Risdayah (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2021)
The purpose of this study was to find out the model of community economic empowerment through home industry, how the process carried out by the Cilampeni Village community related to economic empowerment through the cakwe and odading home industry, how the form of community empowerment in Cilampeni Village related to the cakwe and odading home industry, how the results of economic empowerment carried out by the community Cilampeni village through cakwe and odading home industries. This research is a qualitative research. The results showed that the process of community economic empowerment through the home industry of cakwe and odading, namely by raising awareness, training, coaching and mentoring in the manufacture to marketing of cakwe and odading, the form of empowerment was carried out not only for people who joined the home industry but also for people who did not join but have a relationship with the home industry and the results of community economic empowerment are indicated by an increase in income.